PENGARUH STRUKTUR KEPEMILIKAN, KEBIJAKAN DIVIDEN DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2009-2011 - WIYONO, LANY INDRIANA (Kajian Ilmiah Mahasiswa Manajemen, 2013)
The primary goal of the company is to maximize firm value through increased prosperity owners or shareholders, so that shareholders will invest capital to the company. This research aims to examine the effect of dividend policy, ownership structure includes managerial ownership and institutional ownership, and firm size towards value of the firms. This study uses secondary data of 23 companies listed in Indonesia Stock Exchange during the three year period from 2009 to 2011 as the samples and have to meet certain criteria. The results show that institutional ownership, dividend policy and firm size affects firm value. Insider ownership is not only a significant effect on firm value.